MARKET ANALYSIS OF HEALTH CARE ENTITIES - Vilchez Olivares, Percy Antonio (2016)
In the countries, population ́s health care is a central matter, several countries have outlined and implemented health policies and programs that enabled them to improve and reduce the problems of equity in health. This situation has not been distant to the health system in Peru. In 1997 with the Law No. 26790 -Law on the Modernization of Social Security in Health- it was proposed the participation of Health Care Entities as an alternative model of health care in a context of a contributory regime. This new regulation modifies the rules of social security, introducing the Health Care Entities under this regime, where these entities would treat simple layer diseases and EsSalud would focus on care of complex layer diseases.The objective of this research is to analyze the degree of Health Care Entities ́ penetration within the health market, the date of measurement being 2014. The results show that there is a non-significant participation of the Health Care Entities with respect to Universal Assurance System affiliates. Likewise, there is no adequate dynamism in the health system because two EPS (Rimac and Pacifico Salud) concentrate 94.77% of the total number of regular members of the EPS system.